Web based expert system : calculation for body mass index using fuzzy logic / Norhayati Hatin - Hatin, Norhayati (2006)
Body Mass Index (BMI) is a formula to assess a person's body weight relative to height. It's a useful, indirect measure of body composition, because it correlates highly with body fat in most people. In this project, the fiizzy sets of parameter height, weight, age and Body Mass Index using fuzzyTECH V4.13 fuzzy logic toolkit. The Web based Body Mass Index system is being proposed to assist user, doctor or owner of gymnasiimi to determine the status of Body Mass Index. The system also will give recommendation and store the mformation in databases for statistic reporting purposed.